Bridging the Zambesi - White, Landeg. author. aut Link
XVII, 247 p.
Keywords: In 1935, a bridge was opened across the Zambesi delta in Portuguese East Africa. 51 years later, it was blown up by anti-government forces. This book brings together politics, diplomacy, economics, labour history and technology to show how this engineering feat was a disaster of colonial planning.